Prospects of N-Acetylcysteine and Melatonin as Treatments for Tramadol-Induced Renal Toxicity in Albino Rats - Elias Adikwu, Bonsome Bokolo (Tabriz University of Medical Sciences, 2017)
Background: Tramadol (TD) has played an important role in the treatment of pain. However, renal toxicity due to TD abuse is a serious clinical challenge. This study assessed the effects of n-acetylcysteine (NAC) and melatonin (MT) on TD-induced renal toxicity in albino rats. Methods: Rats were randomized into groups and treated with MT (10mg/kg/day), NAC (10mg/kg/day) and TD (15, 30, and 45mg/kg/day) respectively. Rats were pretreated with MT (10mg/kg/day) and NAC (10mg/kg/day) prior to treatment with TD (15, 30, and 45mg/kg/day) intraperitonialy for 7days respectively. Rats were sacrificed, serum extracted and evaluated for creatinine, urea and uric acid. The kidneys were evaluated for malondialdehyde (MDA), superoxide dismutase (SOD), catalase, (CAT), and glutathione (GSH) levels. Results: Treatment with MT and NAC did not produce significant (P>0.05) effects on serum creatinine, urea, uric acid and kidney MDA, SOD, CAT, and GSH levels when compare to saline control. In contrast, serum creatinine, urea, uric acid and kidney MDA levels were increased while kidney SOD, CAT, and GSH levels were decreased significantly (P<0.05) and in a dose-dependent manner in TD-treated rats. Kidneys of TD-treated rats showed varying degrees of damage which were dose-dependent. However, in all evaluated parameters, TD-induced alterations were abrogated in NAC and MT pretreated rats. Abrogations were most evident in rats pretreated with combined doses of NAC and MT. Conclusion: The present study showed prospects of n-acetylcysteine and melatonin as remedies for tramadol associated renal toxicity.